Effects of risperidone on amino acid metabolism, glucose, and kidney function in healthy adults: A pilot randomized controlled trial - Megumi Oshima; Tadashi Toyama; Yusuke Nakade; Sakae Miyagi; Hisayuki Ogura; Shiori Nakagawa; Takahiro Yuasa; Akihiko Koshino; Keisuke Horikoshi; Taichiro Minami; Keisuke Sako; Shunsuke Tsuge; et al. (PLoS ONE, 2025)
d-serine administration prevents kidney damage in murine models of acute kidney injury, and risperidone inhibits the activity of d-amino acid oxidase, which regulate plasma d-amino acid levels. This pilot randomized controlled trial investigated the effects of risperidone on glucose, amino acid metabolism, and kidney function in healthy adults. Healthy adults with a homeostasis model assessment of insulin resistance (HOMA-IR) of ≥ 1.6 and estimated glomerular filtration rate (eGFR) of ≥ 60 mL/min/1.73m 2 were randomly assigned to the risperidone and control groups. The risperidone group received 0.5 mg/day risperidone for 4 days. The primary outcome was mean change in HOMA-IR on day 5, and the secondary outcomes were changes in d-amino acid levels, eGFR, and urinary albumin. Seven participants were randomized to the risperidone and control groups. The changes in HOMA-IR, eGFR, and urinary albumin on day 5 were not significantly different between the two groups (all p > 0.05). Mean changes in plasma d-serine level and urinary d-serine/creatinine ratio were significantly higher in the risperidone group than in the control group (0.2 vs. −0.3 nmol/mL, p = 0.03 and 38.2 vs. −25.8 nmol/mL, p = 0.01, respectively). Short-term risperidone affects d-serine metabolism without instigating acute adverse effects on kidney or glucose homeostasis in healthy individuals. Clinical Trial Registry number: This study was registered with the Japan Registry for Clinical Trials (jRCTs041210165).